The Italian compassionate use of sofosbuvir observational cohort study for the treatment of recurrent hepatitis C: clinical and virological outcomes. (7th September 2017) - Carrai, Paola; Morelli, Cristina; Cordone, Gabriella; Romano, Antonietta; Tamé, Mariarosa; Lionetti, Raffaella; Pietrosi, Giada; Lenci, Ilaria; Piai, Guido; Russo, Francesco Paolo; Coppola, Carmine; Melazzini, Mario; et al.
Summary: Direct antivirals are available for treating recurrent hepatitis C (RHC). This study reported outcomes of 424 patients with METAVIR F3–F4 RHC who were treated for 24 weeks with sofosbuvir/ribavirin and followed for 12 weeks within the Italian sofosbuvir compassionate use program. In 55 patients, daclatasvir or simeprevir were added. Child–Pugh class and model of end stage liver disease (MELD) scores were evaluated at baseline and 36 weeks after the start of therapy. The sustained viral response (SVR) was 86.7% (316/365) in patients who received sofosbuvir/ribavirin and 98.3% (58/59) in patients who received a second antiviral ( P < 0.01). In patients treated with sofosbuvir/ribavirin, a significant difference in SVR was observed between patients diagnosed with METAVIR F4 (211/250; 84.4%), METAVIR F3 (95/105; 90.5%) and fibrosing cholestatic hepatitis (10/10; 100%) ( P = 0.049). A significant association was found between patients who worsened from Child–Pugh class A and who experienced viral relapse (4/26 vs. 8/189, P = 0.02). In patients with a baseline MELD score <15, a significant association was found between maintaining a final MELD score <15 and the achievement of SVR (187/219 vs. 6/10, P = 0.031). This real‐world study indicates that sofosbuvir/ribavirin treatment for 24 weeks was effective, and the achievement of SVR was associated with a reduced probability of developing worsening liver function.